The Analysis of Casual Factors Affecting Sustainable Growth of Listed Companies on the Stock Exchange of Thailand - Chuamaungphan , Orawon; Chuachoo , Montree (Journal of Management Science Chiangrai Rajabhat University, 2021)
This research study aims to analyze the causal factors affecting the sustainable growth of companies listed on the Stock Exchange of Thailand. The quantitative research method was employed in this study. The samples used in this research method were all of industrial companies listed on the Stock Exchange of Thailand from 2013-2017. The research population included 537 companies, but only 334 companies met the criteria. The study used a linear structural equation model for path analysis using a software program. The study found that the quality of an audit, ownership structure, and a good internal control system had a negative relationship to earning management. This was due to good internal control systems or quality auditing which could decrease earning management. If the business had an ownership structure, foreign investors or trading investors, it would have good corporate governance which could decrease earning management. This study also found that earning management had a negative relationship to sustainable growth. This means that the cost of capital which came mainly from debts would allow the business to expand and have liquidity in the operation, enabling the business to grow continuously and sustainably. However, this study did not find the relationship of capital structure affects earning management. It also did not find a relationship between internal control systems and earning management. In addition, it did not find any impact of internal control systems upon sustainable growth.